Interview with Mr. Miguel Soler Gracia, first and foremost, a Teacher of Secondary Education (Mathematics) - Rojas Martín, Mª del Rosario; Centelles Badenes, Guillem; Rodríguez Bravo, Marcos (Avances en Supervisión Educativa, 2025)
Entrevista a Miguel Soler Gracia.